Cyclopropanation of Various Substrates via Simmons-Smith and Michael-Initiated Ring Closure (MIRC) Reactions - Yudhi Dwi Kurniawan; Duen Ren Hou (Chemistry Department, The University of Brawijaya, 2016)
Cyclopropanation of various electron rich and electron deficient olefins via Simmons-Smith and Michael-initiated ring closure reactions was studied in our research. Cinnamyl alcohol 18 was succesfully cyclopropanated in a good to excellent yield using Simmons-Smith reactions. Methyl and benzyl crotonate 14 and 16 were labile in MIRC reaction condition indicated by the detection of starting material degradation in the NMR spectra of the crude reactions, and allowed a low to moderate product yield. The other starting materials, i.e., cinnamaldehyde 19, methyl cinnamate 20, mono- and di-protected cross-coupled product (4R,5R,E)-methyl 5-(tert-butyldimethylsilyloxy)-4-hydroxyhepta-2,6-dienoate 25 and (4R,5R,E)-methyl 5-(tert-butyldimethylsilyloxy)-4-(methoxymethoxy)hepta-2,6-dienoate 26, were apparently incompatible to the reaction condition set in our study.